2018
DOI: 10.15789/1563-0625-2018-6-855-864
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL AND IMMUNOLOGICAL COMPARISONS IN Th- DEPENDENT IMMUNE RESPONSE MECHANISMS AMONG PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE

Abstract: Chronic obstructive pulmonary disease (COPD) is a global public health problem. Studies in immunological features and their correlations with clinical course of COPD are of importance. The aim of this study was to elucidate clinical and immunological features in COPD of different severity grade, concerning Th1- and Тh17-dependent types of immune response.The study included 132 COPD patients and 32 healthy individuals. According to clinical and functional patterns, the patients with COPD were divided into 3 gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
(20 reference statements)
0
4
0
1
Order By: Relevance
“…Currently, it is generally accepted that COPD is a heterogeneous disease that includes several phenotypes characterized by different clinical manifestations and pathophysiological reactions [ 3 5 , 39 ]. According to modern concepts, COPD phenotypes can be differentiated based on cytokine profiles associated with the development of a certain type of Th immune response [ 6 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is generally accepted that COPD is a heterogeneous disease that includes several phenotypes characterized by different clinical manifestations and pathophysiological reactions [ 3 5 , 39 ]. According to modern concepts, COPD phenotypes can be differentiated based on cytokine profiles associated with the development of a certain type of Th immune response [ 6 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown that Th1 and Th17 types of immune response determine the clinical course of COPD. It has been found that inflammation developing according to the Th17 type of immune response is characterized by more pronounced airway obstruction and a higher risk of infectious complications compared to Th1-dependent inflammation [ 39 ]. Solleiro-Villavicencio et al showed that biomass smoke-induced COPD is associated with the Th2 cytokine profile [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In COPD, a predominance of Th1 and Th17 types of immune response has been detected. 47,48 Moreover, Th17-associated inflammation is characterized by severe airway obstruction and a high risk of infectious complications. 48 A lot of researchers argue that an imbalance between subpopulations of Th17 cells and Tregs promotes COPD progression.…”
Section: Tlr2 and Tlr4 In The Formation Of T-helper Immune Response Imentioning
confidence: 99%
“…47,48 Moreover, Th17-associated inflammation is characterized by severe airway obstruction and a high risk of infectious complications. 48 A lot of researchers argue that an imbalance between subpopulations of Th17 cells and Tregs promotes COPD progression. [49][50][51] There is more evidence of the contribution of TLRs in the formation of Th immune response, including the regulation of Th17/Treg balance.…”
Section: Tlr2 and Tlr4 In The Formation Of T-helper Immune Response Imentioning
confidence: 99%
“…Было установлено, что у пациентов с неосложненным течением болезни, с редкими сезонными обострениями и умеренной степенью ограничения скорости воздушного потока, преобладает Тh1-тип иммунного ответа с характерным для него цитокиновым фоном и субпопуляционным составом лимфоцитов в крови (повышение концентрации TNFα, IFNγ и количества CD3 + CD126 + -клеток, экспрессирующих IL-6R). У больных со средней степенью ограничения скорости воздушного потока, выраженным влиянием ХОБЛ на качество жизни и частыми обострениями превалировал Th17-фенотип иммунного ответа на фоне высокой концентрации IL-21, IL-6 и TGF-β1 в крови и численное преобладание CD4 + CD126 + -лимфоцитов) [21][22][23].…”
Section: патогенетические факторы коморбидности хронической обструктиunclassified